High blood lead concentrations in captive Tasmanian devils (Sarcophilus harrisii): a threat to the conservation of the species?. Issue 11 (28th October 2018) - Hivert, LG; Clarke, JR; Peck, SJ; Lawrence, C; Brown, WE; Huxtable, SJ; Schaap, D; Pemberton, D; Grueber, CE
Abstract : Background: The Tasmanian devil ( Sarcophilus harrisii ) is the world's largest extant marsupial carnivore. Since the emergence of devil facial tumour disease in 1996, the species has undergone a severe population decline. The insurance population (IP) was established in 2006 to build a disease‐free captive population to maintain 95% of the wild Tasmanian devil genetic diversity for 50 years. Captive and semi‐wild Tasmanian devils are fed with possum and wallaby meat provided by local hunters, who use lead ammunition. Lead ingestion can cause acute toxicity, including ataxia, coma and death, or chronic subclinical deleterious effects including decreased fertility. Methods: We determined blood lead concentrations in 26 captive and 133 wild Tasmanian devils from various sites across Tasmania. Results: Captive Tasmanian devils showed significantly higher blood lead concentrations than their conspecifics in the wild. In captivity, older animals had higher blood lead concentrations than young animals, which suggested regular exposure, as lead can accumulate in a living organism in the blood, soft tissues and bones. After a response measure was implemented by removing the heads and wounds containing lead from the diet, blood concentrations significantly decreased in animals at one of the captive study sites, supporting the suspicion of food as the source of lead. Conclusion: This study highlights the need to ensure meat fed to captive carnivores is not contaminated by lead, especially in the context of a conservation program breeding individuals in captivity, as for Tasmanian devils.